Multiple regression equations for predicting different constituents and nitrogen fractions of goat milk - KOUSHKI, M R; GUPTA, M P; OGRA, J L (The Indian Journal of Animal Sciences, 2013)
Multiple regression equations have been developed which are significantly fit to predict the quantityÂ of any of the milk constituents in Jamunapari and Barbari goat milk. These equations are: x1 = Inlercept+(rc2)(x2)+(rc3)(x3)+(rc4) (x4)+(rc5)(x5)+(rc6)(x6)+(rc7)(x7)+(rc8)(x8)+(rc9)(x9)+(rc10)(x10). Where. rc2 ....... rc9 and rc10 are regression coefficients. x1 is yield. x2 is specific gravity, x3 is acidity, x4 is chloride, x5 18 TS, x6 is SNF, x7 is fat, x9 is lactose, x9 is ash and x11 is energy.Â The multiple regression equations have also been developed which are significantly fit to predict the quantity of any of me nitrogen fraction in Jamunapari and Barbari milk. x1 =Intercept + (rc2)(x2)+(rc3)(x3)+(re4)(x4)+(re5)(x5)+(re6)(x6)+(c7)(x7)+(rc8)(x8)+(re9)(x9)Where, rc2,re3...... re9 and rc10 are regression coefficients, x1 is total N, x2 is NPN, x3 is protein N4 x4 is casein N5 x5 is whey protein N6 x6 is total albumin N7 x7 is Beta lactoglobulin N8 x8 is residual albumin N9 x9 is proteose-peptone N10 and x10 is globulin N.